2022
DOI: 10.3390/land11081131
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Spatial-Temporal Characteristics of Inclusive Green Growth in China

Abstract: In the context of the widely recognized concept of inclusive green growth, it is of great practical significance to study the measurement of inclusive green growth, its temporal characteristics and its spatial heterogeneity. However, it should be noted that most existing studies only consider the situation of China when constructing inclusive green growth indices, and such studies lack international comparators. The index selection dimension is relatively single, and the temporal characteristics and spatial he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…To eliminate the influence of different measurement units and make the results more comparable, the original indicators are normalized by the min–max method. Consistent with Zhou and Wu (2018) and Gu et al (2021), the fixed base range entropy weight method is employed to calculate the weights of indicators, and the detailed calculation is described in the Appendix. The calculation results of inclusive green growth are shown in the following figure (see Figure 3).…”
Section: Methodology: Models Variables and Datamentioning
confidence: 99%
“…To eliminate the influence of different measurement units and make the results more comparable, the original indicators are normalized by the min–max method. Consistent with Zhou and Wu (2018) and Gu et al (2021), the fixed base range entropy weight method is employed to calculate the weights of indicators, and the detailed calculation is described in the Appendix. The calculation results of inclusive green growth are shown in the following figure (see Figure 3).…”
Section: Methodology: Models Variables and Datamentioning
confidence: 99%
“…), which found that Internet development significantly contributed towards the enhancement of total factor carbon productivity [ 45 ]. Zhao’ s study (2022) is concerned with inclusive economic growth and focuses mainly on the analysis of the intrinsic drivers of inclusive economic growth [ 46 ]. Li and Song’s study (2022) constructs a green evaluation system based on three dimensions: economic, environmental, and social and investigates its intrinsic mechanisms [ 47 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the micro level, Zhang Xun et al ( 2020) conducted an empirical study using micro-household data and found that the development of DIFI contributes to inclusive growth in China by increasing household income, especially for rural low-income groups. Xie, Gai-Li et al (2018) studied the impact of DIFI on entrepreneurship and found that the total digital finance index as well as the three first-order dimension indicators significantly promoted entrepreneurship [7][8].…”
Section: Review Of the Literaturementioning
confidence: 99%